Prevalence and Risk Factors Associated with Dermatophytosis in the one Humped Camel (Camelus Dromedarius) Dairy Farms in Benadir Region, Somalia (Global Journal of Medical Research, 2022)
Ringworm is zoonotic skin disease and one of the most frequently occurring in human and domesticated animals. It is estimated that 20% of the world population is affected by Ringworm. Camel Dermatophytosis has great public health and economic impact that leads to low milk yield, meat production and poor hide quality. A cross-sectional study was carried out to determine the prevalence and risk factors associated with Ringworm infection among One- humped camel (Camelus dromedarius) in Camel farms of Benadir Region, Somalia. 384 camels surveyed from camel farms randomly were screened in Ringworm infection. 54 camels (14%) were clinically suspected by examining skin scrapings in 20% KOH for detection of Ringworm under the microscope. Among this 29 camels (7.5%) were infected with Ringworm. According to the age group the highest prevalence was recorded camels younger than 3 years.
Keywords: dermatophytosis; camel; public health; KOH